The membrane structure and function affected by water. (July 2019) - Kučerka, Norbert; Gallová, Jana; Uhríková, Daniela
Highlights: Water impacts the proper functioning of biological membranes. Hydration shell of ions affects their interactions with lipid bilayers. Hydrogen bonding with water promotes cholesterol to localize in the bilayer center. Water encroachment into lipid bilayer increases with the addition of long chain aliphatic alcohols. Water is the most prevalent biomolecule in membrane systems. Abstract: Various experimental data reveal intriguing peculiarities in structural properties of biomimetic membranes. Interestingly, one of the common alterations that is observed at the membrane-water interface underlines the important role of membrane hydration properties. A plausible mechanism of action in the case of many membrane additives seems to be in shifting the water encroachment the way that bilayers absorb more or less water molecules - one of the smallest and often neglected biomolecule. The difference in water interactions with different lipids and cholesterol has been noted at the interface and up to the bilayer center, the ion depending interplay between lipid-water and ion-water hydrations has been shown, and the anaesthetic effect also appears to link tightly to hydration, to discuss but a few examples. Although a complete understanding of the physicochemical processes taking place in biomembranes is not established fully, the understanding of lipid bilayer structural changes as a result of different properties of environment outside and/or inside the membrane provides a foundation for better insights into the structure-function relationships that most certainly take place in complex biomembrane systems.